Assessing clinical probability of pulmonary embolism: prospective validation of the simplified Geneva score. (17th August 2017) - Robert‐Ebadi, H.; Mostaguir, K.; Hovens, M. M.; Kare, M.; Verschuren, F.; Girard, P.; Huisman, M. V.; Moustafa, F.; Kamphuisen, P. W.; Buller, H. R.; Righini, M.; Le Gal, G.
Abstract : Essentials The simplified Geneva score allows easier pretest probability assessment of pulmonary embolism (PE). We prospectively validated this score in the ADJUST‐PE management outcome study. The study shows that it is safe to manage patients with suspected PE according to this score. The simplified Geneva score is now ready for use in routine clinical practice. Summary: Background: Pretest probability assessment by a clinical prediction rule (CPR) is an important step in the management of patients with suspected pulmonary embolism (PE). A limitation to the use of CPRs is that their constitutive variables and corresponding number of points are difficult to memorize. A simplified version of the Geneva score (i.e. attributing one point to each variable) has been proposed but never been prospectively validated. Aims: Prospective validation of the simplified Geneva score (SGS) and comparison with the previous version of the Geneva score (GS). Methods: In the ADJUST‐PE study, which had the primary aim of validating the age‐adjusted D‐dimer cut‐off, the SGS was prospectively used to determine the pretest probability in a subsample of 1621 study patients. Results: Overall, PE was confirmed in 294 (18.1%) patients. Using the SGS, 608 (37.5%), 980 (60.5%) and 33 (2%) were classified as having a low, intermediate and high clinical probability. Corresponding prevalences of PE were 9.7%, 22.4% and 45.5%; 490 (30.1%) patients with low or intermediate probability had a D‐dimer level below 500 μg L −1 and 653 (41.1%) had a negative D‐dimer test according to the age‐adjusted cut‐off. Using the GS, the figures were 491(30.9%) and 650 (40.9%). None of the patients considered as not having PE based on a low or intermediate SGS and negative D‐dimer had a recurrent thromboembolic event during the 3‐month follow‐up. Conclusions: The use of SGS has similar efficiency and safety to the GS in excluding PE in association with the D‐dimer test.